Consumo de sustancias psicotrópicas durante la gestación y su influencia en recién nacidos en el Hospital General Martin Icaza en el periodo noviembre 2023- abril 2024. - Carrillo Pérez, Engy Iliana (2024)
The problem of this research project focuses on the consumption of psychotropic substances during pregnancy and how these influence the newborn, which usually occurs in adolescent patients, or in patients who have been consuming these substances since their adolescence and reach the age of Martin Icaza General Hospital, generally inhabitants of urban, rural and marginal urban areas. In this study, types of research such as descriptive and field research are applied in order to understand the factors associated with the consumption of psychotropic substances in pregnant women, describing in turn the most common types of psychotropic substances consumed during pregnancy and the effects that will have these on fetal development and the health of the newborn. At the same time, research methodologies such as the inductive and deductive method, since, by collecting data through interviews with the patient and review of medical records, data can be recorded on the pregnant women and, in turn, on the neonates. Likewise, through bibliographic research, information is collected, thus carrying out an analysis of the object of study on the complications and diseases that occur in the pregnant woman and the newborn, such as withdrawal syndrome, and different pathologies due to drug consumption.